Polarizer processing technology

Through the precision controlled multi-step processing technology, the problems of complex and unstable performance of traditional polarizer preparation processes are solved, and high-quality, stable and environmentally friendly polarizer production is achieved.

CN119511437APending Publication Date: 2025-02-25XUZHOU LIANCHAO PHOTOELECTRIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411734381.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The preparation process of traditional polarizers is complex, and multiple processing and testing processes are difficult to control, resulting in low yield and performance degradation due to environmental changes during long-term use.

Method used

A multi-step polarizer processing technology is adopted, including polishing sheet preparation, coating treatment, glueing and curing, UV film covering and cutting, and micraulic sheet bonding. The high quality and stability of the product are ensured by precise control of each process parameter.

Benefits of technology

It improves the service life and performance stability of the polarizer, enhances performance parameters such as polarization, transmittance, optical compensation value, peel intensity and thermal expansion coefficient, reduces production costs and reduces the impact on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119511437A_ABST
    Figure CN119511437A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polaroid processing, in particular to a polaroid processing technology which comprises the following steps: preparing a white glass raw material and preparing a polished wafer; the appearance and thickness of the polished wafer are detected, and the surface energy of the polished wafer is enhanced after the polished wafer is cleaned and dedusted; carrying out intermediate coating operation on the white glass 1 and the white glass 2 after the surface energy is enhanced, and further carrying out appearance detection; according to the technology, through multiple cleaning and multiple inspection operations, the overall service life of the polaroid is better prolonged, the overall polarization effect is improved through gluing, curing and cutting operations, real-time supervision on the overall process is facilitated, when a problem occurs in a certain link, rapid positioning and processing can be conducted, unnecessary losses are reduced, and the production efficiency is improved. And through multiple reliability experiment tests, the stability and reliability in practical application are guaranteed, meanwhile, recyclable materials are adopted in the technological process, and the influence on the environment is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polarizing plate processing, in particular to a polarizing plate processing technology. Background Art

[0002] A polarizer is an optical element that can selectively transmit or block light wave vibrations in a specific direction. It can only allow light waves in a specific direction to pass through, thereby controlling the direction of light wave vibrations. It has a wide range of applications in many fields, including but not limited to display technology, photography and videography, optical instruments, and scientific research and industrial applications.

[0003] However, in general, the preparation process of traditional polarizers usually involves coating the glass slides and then assembling and packaging them, which involves multiple processing and distribution detection processes. Multiple variables in the process are difficult to control, so the yield rate is often limited. Moreover, during the long-term use of polarizers, it is difficult to guarantee and avoid performance degradation caused by the environment without specific adhesive material ratios and sampling tests.

[0004] Based on this, the present invention provides a polarizing plate processing technology to solve the above-mentioned technical problems. Summary of the invention

[0005] The object of the present invention is to provide a polarizing plate processing technology for solving the problems raised by the above background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A polarizing plate processing process comprises the following steps:

[0008] S1. Prepare white glass raw materials and prepare polished sheets;

[0009] S2. Perform appearance and thickness inspection on the polishing sheet, and enhance the surface energy of the polishing sheet after cleaning and dust removal;

[0010] S3. Performing a coating operation on the white glass 1 and the white glass 2 after the surface energy enhancement in step S2 and further performing an appearance inspection;

[0011] S4. Prefabricating a polarizing film and configuring a specific ratio of adhesive, bonding and curing the polarizing film after cleaning and coating the white glass 1 and the white glass 2 by preparing a specific ratio of adhesive;

[0012] S5. Cover the white glass 1 and the white glass 2 with the polarizing film in step S4 with a UV film and perform a knife wheel cutting;

[0013] S6. Pre-treating the polarizer coated with UV film and cut in step S5;

[0014] S7. Laminating and curing the polarizer pretreated in step S6 with Mylar sheets, and packaging and storing;

[0015] S8. Select 1-2 batches from every 100 batches of polarizer products entering the warehouse for performance testing and reliability testing.

[0016] As a preferred technical solution of the present invention, the implementation steps of step S1 are:

[0017] S1.1. Use high-purity silicate glass original sheets, the thickness of white glass 1 is 0.30±0.015mm, the thickness of white glass 2 is 0.55±0.015mm, ensure there are no bubbles or scratches, use an optical detector to detect the glass surface quality, and ensure that the transmittance is ≥92%;

[0018] S1.2. Use a precision diamond wheel to cut the glass sheet into 100mm×100mm to 200mm×200mm with a cutting accuracy of 0.05mm, and then perform edge chamfering with a chamfer angle of 45° and a chamfer width of 0.1mm to reduce the risk of breakage in subsequent processing;

[0019] S1.3. Prepare a polishing solution containing SiO2 particles with a particle size of 0.5 μm and a surfactant, the ratio of the polishing solution to the surfactant is 50 grams per liter of solution, and the pH value is controlled at 7.0 ± 0.5 to ensure the polishing effect;

[0020] S1.4. Use a double-sided polishing machine and set the speed to 1500rpm, the polishing time to 30min, and the pressure to 20kPa to polish white glass 1 and white glass 2, ensuring that the glass surface roughness Ra≤0.01μm and the light transmittance is greater than 94%;

[0021] S1.5. Use an ultrasonic cleaner to clean the polished white glass 1 and white glass 2 three times with deionized water and anhydrous ethanol alternately for 5 minutes each time to remove polishing residues. After cleaning, dry them in an oven at 60°C for 1 hour.

[0022] As a preferred technical solution of the present invention, the implementation steps of step S2 are:

[0023] S2.1. Use a 10x magnifying glass to check the surface of the polished sheet to ensure there are no cracks or scratches;

[0024] S2.2. Use a micrometer to measure the thickness of each piece of glass, ensuring that the thickness of white glass 1 is 0.30±0.015mm and that of white glass 2 is 0.55±0.015mm;

[0025] S2.3. Immerse the polishing sheet in a dilute hydrochloric acid solution with a pH of 2.5 for 5 minutes to remove metal ion contamination, and then neutralize it with a dilute sodium hydroxide solution with a pH of 10.5 for 3 minutes;

[0026] S2.4. Rinse with deionized water three times, 2 minutes each time, to ensure that there is no residual acid or alkali, then air dry naturally in a dust-free environment or blow dry with nitrogen, and wipe the surface with a dust-free cloth;

[0027] S2.5. Treat the surface with a plasma processor at 100W for 10 seconds to enhance the adhesion of subsequent coatings.

[0028] As a preferred technical solution of the present invention, the implementation steps of step S3 are:

[0029] S3.1. Place the polished sheets of white glass 1 and white glass 2 on the stage of the vacuum coating machine and evacuate to 10-4Pa;

[0030] S3.2. MgF2 with high light transmittance and low refractive index and a thickness of 50 nm was selected as the coating material. The coating time was 5 min under the coating process parameters of electron beam energy of 20 kV and evaporation rate of 0.1 nm / s. The film was then cured at 150°C for 30 min to enhance the stability of the film.

[0031] S3.3. Use a 50x optical microscope to check the uniformity of the coating, including peeling and cracking;

[0032] S3.4. Use a transmittance tester to ensure that the transmittance after coating is greater than 93%, and measure the surface roughness again to ensure that Ra ≤ 0.02μm.

[0033] As a preferred technical solution of the present invention, the implementation steps of step S4 are:

[0034] S4.1. Select a 0.215 mm thick polyvinyl alcohol polarizing film and cut it to a size that matches the coated white glass 1 and white glass 2;

[0035] S4.2. Soak the polarizing film in anhydrous ethanol for 5 min, and then rinse it with deionized water twice, 1 min each time;

[0036] S4.3. Place the polarizing film between the white glass 1 and the white glass 2 and perform a composite operation by using an adhesive. The specific bonding structure is as follows:

[0037] Clear glass 1+polarizing film+clear glass 2;

[0038] Apply the adhesive, use a vacuum press, set the pressure to 0.5MPa, and the time to 15min, and initially cure in a 60℃ oven for 2 hours. After the time is up, raise the temperature to 80℃ and cure for another 4 hours to ensure that the adhesive is completely cured;

[0039] S4.4. Use a diamond grinding wheel to trim the edges and ensure that the finished product size specification is 1.10±0.015mm.

[0040] As a preferred technical solution of the present invention, the adhesive in step S4 is specifically obtained by mixing T-31 phenolic amine (PAA) and epoxy curing agent in a ratio of epoxy resin: curing agent of 100:5.

[0041] As a preferred technical solution of the present invention, the implementation steps of step S5 are:

[0042] S5.1. Select a 0.05 mm thick UV curing film and cut it to a size that matches the polarizer, and ensure that it is consistent with the finished product size in step S4;

[0043] S5.2. Apply a layer of UV glue evenly on the surface of the polarizer and compact it with a roller. The coating ratio of UV glue is 50 grams per square meter.

[0044] S5.3. Use a UV curing machine, set the wavelength to 365nm and the energy density to 1000mJ / cm 2 , perform a 10-second curing operation;

[0045] S5.4. Use a precision diamond wheel with a cutting accuracy of 0.02 mm to cut the polarizer to the finished size, grind the cut edge with a fine grinding wheel to ensure smoothness and no burrs, and wipe the surface with a dust-free cloth moistened with 1 / 3 of anhydrous ethanol to remove debris generated by cutting;

[0046] S5.5. Use a vernier caliper to measure the finished product size and ensure that the specification is 1.10±0.015mm.

[0047] As a preferred technical solution of the present invention, the implementation steps of step S6 are:

[0048] S6.1. Use a plasma processor with a power of 80W to perform surface activation treatment for 5 seconds to increase surface energy for subsequent bonding;

[0049] S6.2. Spray antistatic agent and let it stand for 5 minutes to ensure that the surface resistivity is less than 10^9Ω;

[0050] S6.3. Use a magnifying glass to check the surface to ensure that there are no foreign objects or scratches. Then prepare the Mylar sheet and cut it to a size that matches the polarizer with an error range of ±0.05mm. Align the Mylar sheet with the polarizer and fit them together at a pressure of 0.1±0.05MPa to ensure that there are no bubbles. Use epoxy resin glue to seal the edges to prevent water vapor intrusion.

[0051] As a preferred technical solution of the present invention, the implementation steps of step S7 are:

[0052] S7.1. Attach the Mylar sheet to the surface of the polarizer and use a vacuum press to press for 10 minutes at a pressure parameter of 0.3 MPa;

[0053] S7.2. Curing in a 60°C oven for 1 hour to ensure a firm fit;

[0054] S7.3. Use an anti-static packaging bag that is slightly larger than the polarizer. Make sure the bag can completely wrap the polarizer and have enough space for sealing. Put the polarizer into the bag and seal it with a heat sealer.

[0055] S7.4. Use a transmittance tester to test the transmittance. The qualified standard is whether it is greater than 90%. Put the packaged and qualified polarizers in a dry and ventilated warehouse with an ambient temperature of 20-25℃ and a humidity of 40-60%.

[0056] As a preferred technical solution of the present invention, the performance test in step S8 includes polarization, transmittance, optical compensation value, peel strength and thermal expansion coefficient test, and the reliability test in step S8 includes water boiling film drawing, high temperature storage, low temperature storage, high and low temperature storage and hot and cold shock test.

[0057] Compared with the prior art, the present invention has the following beneficial effects:

[0058] The process of the present invention improves the overall service life of the polarizer by performing multiple cleaning and multiple inspection operations, improves the overall polarization effect by gluing, curing and cutting operations, facilitates real-time supervision of the overall process, and can quickly locate and handle problems when a certain link occurs, thereby reducing unnecessary losses. The polarizer prepared by the above process has better performance parameters such as polarization degree, transmittance, optical compensation value, peel strength and thermal expansion coefficient, and has undergone multiple reliability experimental tests to ensure stability and reliability in practical applications. At the same time, recyclable materials are used in the process of the present invention to reduce the impact on the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 The flowchart of the polarizing plate processing process of the present invention is shown. DETAILED DESCRIPTION

[0060] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] 1. Materials:

[0062] The high-purity silicate glass original sheet, SiO2 particles, polyvinyl alcohol polarizing film and UV curing film of the present invention are all purchased from the market unless otherwise specified.

[0063] 2. Process:

[0064] See also Figure 1 The present invention provides a polarizing plate processing technology, which specifically includes the following steps:

[0065] S1. Prepare white glass raw materials and prepare polishing sheets. Specifically, the steps are as follows:

[0066] S1.1. Use high-purity silicate glass original sheets, the thickness of white glass 1 is 0.30±0.015mm, the thickness of white glass 2 is 0.55±0.015mm, ensure there are no bubbles or scratches, use an optical detector to detect the glass surface quality, and ensure that the transmittance is ≥92%;

[0067] S1.2. Use a precision diamond wheel to cut the glass sheet into 100mm×100mm to 200mm×200mm with a cutting accuracy of 0.05mm, and then perform edge chamfering with a chamfer angle of 45° and a chamfer width of 0.1mm to reduce the risk of breakage in subsequent processing;

[0068] S1.3. Prepare a polishing solution containing SiO2 particles with a particle size of 0.5 μm and a surfactant, the ratio of the polishing solution to the surfactant is 50 grams per liter of solution, and the pH value is controlled at 7.0 ± 0.5 to ensure the polishing effect;

[0069] S1.4. Use a double-sided polishing machine and set the speed to 1500rpm, the polishing time to 30min, and the pressure to 20kPa to polish white glass 1 and white glass 2, ensuring that the glass surface roughness Ra≤0.01μm and the light transmittance is greater than 94%;

[0070] S1.5. Use an ultrasonic cleaner to clean the polished white glass 1 and white glass 2 three times with deionized water and anhydrous ethanol alternately for 5 minutes each time to remove polishing residues. After cleaning, dry them in an oven at 60°C for 1 hour.

[0071] S2. Perform appearance and thickness inspection on the polishing sheet, and enhance the surface energy of the polishing sheet after cleaning and dust removal. Specifically, the steps are as follows:

[0072] S2.1. Use a 10x magnifying glass to check the surface of the polished sheet to ensure there are no cracks or scratches;

[0073] S2.2. Use a micrometer to measure the thickness of each piece of glass, ensuring that the thickness of white glass 1 is 0.30±0.015mm and that of white glass 2 is 0.55±0.015mm;

[0074] S2.3. Immerse the polishing sheet in a dilute hydrochloric acid solution with a pH of 2.5 for 5 minutes to remove metal ion contamination, and then neutralize it with a dilute sodium hydroxide solution with a pH of 10.5 for 3 minutes;

[0075] S2.4. Rinse with deionized water three times, 2 minutes each time, to ensure that there is no residual acid or alkali, then air dry naturally in a dust-free environment or blow dry with nitrogen, and wipe the surface with a dust-free cloth;

[0076] S2.5. Treat the surface with a plasma processor at 100W for 10 seconds to enhance the adhesion of subsequent coatings;

[0077] S3. Performing a coating operation on the white glass 1 and the white glass 2 after the surface energy enhancement in step S2 and further performing an appearance inspection, specifically, the steps are as follows:

[0078] S3.1. Place the polished sheets of white glass 1 and white glass 2 on the stage of the vacuum coating machine and evacuate to 10-4Pa;

[0079] S3.2. MgF2 with high light transmittance and low refractive index and a thickness of 50 nm was selected as the coating material. The coating time was 5 min under the coating process parameters of electron beam energy of 20 kV and evaporation rate of 0.1 nm / s. The film was then cured at 150°C for 30 min to enhance the stability of the film.

[0080] S3.3. Use a 50x optical microscope to check the uniformity of the coating, including peeling and cracking;

[0081] S3.4. Use a light transmittance tester to ensure that the light transmittance after coating is greater than 93%, and measure the surface roughness again to ensure that Ra ≤ 0.02μm;

[0082] S4. Prefabricate the polarizing film and prepare a specific ratio of adhesive. After the polarizing film is cleaned, the prepared specific ratio of adhesive is used to bond and cure the white glass 1 and the white glass 2 after coating. Specifically, the steps are as follows:

[0083] S4.1. Select a 0.215 mm thick polyvinyl alcohol polarizing film and cut it to a size that matches the coated white glass 1 and white glass 2;

[0084] S4.2. Soak the polarizing film in anhydrous ethanol for 5 min, and then rinse it with deionized water twice, 1 min each time;

[0085] S4.3. Place the polarizing film between the white glass 1 and the white glass 2 and perform a composite operation by using an adhesive. The specific bonding structure is as follows:

[0086] Clear glass 1+polarizing film+clear glass 2;

[0087] In this step, it should be noted that the adhesive is specifically obtained by mixing T-31 phenolic amine (PAA) epoxy curing agent in a ratio of 100:5 of epoxy resin: curing agent;

[0088] Apply the adhesive, use a vacuum press, set the pressure to 0.5MPa, and the time to 15min, and initially cure in a 60℃ oven for 2 hours. After the time is up, raise the temperature to 80℃ and cure for another 4 hours to ensure that the adhesive is completely cured;

[0089] S4.4. Use a diamond grinding wheel to trim the edges to ensure that the finished product size specification is 1.10±0.015mm;

[0090] S5. Cover the white glass 1 and the white glass 2 with the polarizing film in step S4 with a UV film and perform a knife wheel cutting. Specifically, the steps are as follows:

[0091] S5.1. Select a 0.05 mm thick UV curing film and cut it to a size that matches the polarizer, and ensure that it is consistent with the finished product size in step S4;

[0092] S5.2. Apply a layer of UV glue evenly on the surface of the polarizer and compact it with a roller. The coating ratio of UV glue is 50 grams per square meter.

[0093] S5.3. Use a UV curing machine, set the wavelength to 365nm and the energy density to 1000mJ / cm 2 , perform a 10-second curing operation;

[0094] S5.4. Use a precision diamond wheel with a cutting accuracy of 0.02 mm to cut the polarizer to the finished size, grind the cut edge with a fine grinding wheel to ensure smoothness and no burrs, and wipe the surface with a dust-free cloth moistened with 1 / 3 of anhydrous ethanol to remove debris generated by cutting;

[0095] S5.5. Use a vernier caliper to measure the finished product size and ensure that the specification is 1.10±0.015mm;

[0096] S6. Pre-processing the polarizer coated with UV film and cut in step S5, specifically, the steps are as follows:

[0097] S6.1. Use a plasma processor with a power of 80W to perform surface activation treatment for 5 seconds to increase surface energy for subsequent bonding;

[0098] S6.2. Spray antistatic agent and let it stand for 5 minutes to ensure that the surface resistivity is less than 10^9Ω;

[0099] S6.3. Use a magnifying glass to check the surface to ensure that there are no foreign objects or scratches. Then prepare the Mylar sheet and cut it to a size that matches the polarizer. The error range is ±0.05 mm. Align the Mylar sheet with the polarizer and fit them together at a pressure of 0.1±0.05 MPa to ensure that there are no bubbles. Use epoxy resin glue to seal the edges to prevent water vapor intrusion.

[0100] S7. The polarizer pretreated in step S6 is subjected to Mylar lamination and curing treatment, and then packaged and stored. Specifically, the steps are as follows:

[0101] S7.1. Attach the Mylar sheet to the surface of the polarizer and use a vacuum press to press for 10 minutes at a pressure parameter of 0.3 MPa;

[0102] S7.2. Curing in a 60°C oven for 1 hour to ensure a firm fit;

[0103] S7.3. Use an anti-static packaging bag that is slightly larger than the polarizer. Make sure the bag can completely wrap the polarizer and have enough space for sealing. Put the polarizer into the bag and seal it with a heat sealer.

[0104] S7.4. Use a transmittance tester to test the transmittance. The qualified standard is whether it is greater than 90%. Put the packaged and qualified polarizers in a dry and ventilated warehouse with an ambient temperature of 20-25℃ and a humidity of 40-60%.

[0105] Example 1

[0106] In this embodiment, a polarizing plate processing process specifically includes the following steps:

[0107] S1. Prepare white glass raw materials and prepare polishing sheets. Specifically, the steps are as follows:

[0108] S1.1. Use high-purity silicate glass sheets, with the thickness of white glass 1 being 0.30mm and the thickness of white glass 2 being 0.55mm, to ensure that there are no bubbles or scratches. Use an optical detector to inspect the glass surface quality to ensure that the light transmittance is ≥ 92%;

[0109] S1.2. Use a precision diamond wheel to cut the glass sheet into 200mm×200mm with a cutting accuracy of 0.05mm, and then perform edge chamfering with a chamfer angle of 45° and a chamfer width of 0.1mm to reduce the risk of breakage in subsequent processing;

[0110] S1.3. Prepare a polishing solution containing SiO2 particles with a particle size of 0.5 μm and a surfactant, the ratio of the polishing solution to the surfactant is 50 grams per liter of solution, and the pH value is controlled at 7.0 to ensure the polishing effect;

[0111] S1.4. Use a double-sided polishing machine and set the speed to 1500rpm, the polishing time to 30min, and the pressure to 20kPa to polish white glass 1 and white glass 2, ensuring that the glass surface roughness Ra≤0.01μm and the light transmittance is greater than 94%;

[0112] S1.5. Use an ultrasonic cleaner to clean the polished white glass 1 and white glass 2 three times with deionized water and anhydrous ethanol alternately for 5 minutes each time to remove polishing residues. After cleaning, dry them in an oven at 60°C for 1 hour.

[0113] S2. Perform appearance and thickness inspection on the polishing sheet, and enhance the surface energy of the polishing sheet after cleaning and dust removal. Specifically, the steps are as follows:

[0114] S2.1. Use a 10x magnifying glass to check the surface of the polished sheet to ensure there are no cracks or scratches;

[0115] S2.2. Use a micrometer to measure the thickness of each piece of glass, ensuring that the thickness of white glass 1 is 0.30 mm and that of white glass 2 is 0.55 mm;

[0116] S2.3. Immerse the polishing sheet in a dilute hydrochloric acid solution with a pH of 2.5 for 5 minutes to remove metal ion contamination, and then neutralize it with a dilute sodium hydroxide solution with a pH of 10.5 for 3 minutes;

[0117] S2.4. Rinse with deionized water three times, 2 minutes each time, to ensure that there is no residual acid or alkali, then air dry naturally in a dust-free environment or blow dry with nitrogen, and wipe the surface with a dust-free cloth;

[0118] S2.5. Treat the surface with a plasma processor at 100W for 10 seconds to enhance the adhesion of subsequent coatings;

[0119] S3. Performing a coating operation on the white glass 1 and the white glass 2 after the surface energy enhancement in step S2 and further performing an appearance inspection, specifically, the steps are as follows:

[0120] S3.1. Place the polished sheets of white glass 1 and white glass 2 on the stage of the vacuum coating machine and evacuate to 10-4 Pa;

[0121] S3.2. MgF2 with high light transmittance and low refractive index and a thickness of 50 nm was selected as the coating material. The coating time was 5 min under the coating process parameters of electron beam energy of 20 kV and evaporation rate of 0.1 nm / s. The film was then cured at 150°C for 30 min to enhance the stability of the film.

[0122] S3.3. Use a 50x optical microscope to check the uniformity of the coating, including peeling and cracking;

[0123] S3.4. Use a light transmittance tester to ensure that the light transmittance after coating is greater than 93%, and measure the surface roughness again to ensure that Ra ≤ 0.02μm;

[0124] S4. Prefabricate the polarizing film and prepare a specific ratio of adhesive. After the polarizing film is cleaned, the prepared specific ratio of adhesive is used to bond and cure the white glass 1 and the white glass 2 after coating. Specifically, the steps are as follows:

[0125] S4.1. Select a 0.215 mm thick polyvinyl alcohol polarizing film and cut it to a size that matches the coated white glass 1 and white glass 2;

[0126] S4.2. Soak the polarizing film in anhydrous ethanol for 5 min, and then rinse it with deionized water twice, 1 min each time;

[0127] S4.3. Place the polarizing film between the white glass 1 and the white glass 2 and perform a composite operation by using an adhesive. The specific bonding structure is as follows:

[0128] Clear glass 1+polarizing film+clear glass 2;

[0129] In this step, it should be noted that the adhesive is specifically obtained by mixing T-31 phenolic amine (PAA) epoxy curing agent in a ratio of 100:5 of epoxy resin: curing agent;

[0130] Apply the adhesive, use a vacuum press, set the pressure to 0.5MPa, and the time to 15min, and initially cure in a 60℃ oven for 2 hours. After the time is up, raise the temperature to 80℃ and cure for another 4 hours to ensure that the adhesive is completely cured;

[0131] S4.4. Use a diamond grinding wheel to trim the edges to ensure that the finished product size specification is 1.1mm;

[0132] S5. Cover the white glass 1 and the white glass 2 with the polarizing film in step S4 with a UV film and perform a knife wheel cutting. Specifically, the steps are as follows:

[0133] S5.1. Select a 0.05 mm thick UV curing film and cut it to a size that matches the polarizer, and ensure that it is consistent with the finished product size in step S4;

[0134] S5.2. Apply a layer of UV glue evenly on the surface of the polarizer and compact it with a roller. The coating ratio of UV glue is 50 grams per square meter.

[0135] S5.3. Use a UV curing machine, set the wavelength to 365nm and the energy density to 1000mJ / cm 2 , perform a 10-second curing operation;

[0136] S5.4. Use a precision diamond wheel with a cutting accuracy of 0.02 mm to cut the polarizer to the finished size, grind the cut edge with a fine grinding wheel to ensure smoothness and no burrs, and wipe the surface with a dust-free cloth moistened with 1 / 3 of anhydrous ethanol to remove debris generated by cutting;

[0137] S5.5. Use a vernier caliper to measure the finished product size and ensure that the specification is 1.10mm;

[0138] S6. Pre-processing the polarizer coated with UV film and cut in step S5, specifically, the steps are as follows:

[0139] S6.1. Use a plasma processor with a power of 80W to perform surface activation treatment for 5 seconds to increase surface energy for subsequent bonding;

[0140] S6.2. Spray antistatic agent and let it stand for 5 minutes to ensure that the surface resistivity is less than 10^9Ω;

[0141] S6.3. Use a magnifying glass to check the surface to ensure that there are no foreign objects or scratches. Then prepare the Mylar sheet and cut it to a size that matches the polarizer. The error range is ±0.05mm. Align the Mylar sheet with the polarizer and fit them together under a pressure of 0.1MPa to ensure that there are no bubbles. Use epoxy resin glue to seal the edges to prevent water vapor from intruding.

[0142] S7. The polarizer pretreated in step S6 is subjected to Mylar lamination and curing treatment, and then packaged and stored. Specifically, the steps are as follows:

[0143] S7.1. Attach the Mylar sheet to the surface of the polarizer and use a vacuum press to press for 10 minutes at a pressure parameter of 0.3 MPa;

[0144] S7.2. Curing in a 60°C oven for 1 hour to ensure a firm fit;

[0145] S7.3. Use an anti-static packaging bag that is slightly larger than the polarizer. Make sure the bag can completely wrap the polarizer and have enough space for sealing. Put the polarizer into the bag and seal it with a heat sealer.

[0146] S7.4. Use a transmittance tester to test the transmittance. The qualified standard is whether it is greater than 90%. Put the packaged and qualified polarizers in a dry and ventilated warehouse with an ambient temperature of 20°C and a humidity of 40%;

[0147] The polarizing plate is manufactured through the above process.

[0148] Comparative Example 1

[0149] In this comparative example 1, step S1.1 uses high-purity silicate glass original sheets, the thickness of white glass 1 is 0.315mmmm, and the thickness of white glass 2 is 0.565mm, ensuring that there are no bubbles or scratches, and using an optical detector to detect the surface quality of the glass to ensure that the transmittance is ≥92%;

[0150] The remaining steps and parameters are the same as those in Example 1 to obtain a polarizing plate 1.

[0151] Comparative Example 2

[0152] In this comparative example 2, step S1.4 uses a double-sided polishing machine, and sets the speed to 1500 rpm, the polishing time to 35 min, and the pressure to 20 kPa to polish the white glass 1 and the white glass 2, ensuring that the glass surface roughness Ra ≤ 0.01 μm and the light transmittance is greater than 94%;

[0153] The remaining steps and parameters are the same as those in Example 1 to obtain a polarizing plate 2.

[0154] Comparative Example 3

[0155] In this comparative example 3, step S3.2 selects MgF2 with high light transmittance and low refractive properties and a thickness of 50 nm as the coating material, and the coating time is 6 minutes under the coating process parameters of electron beam energy 20 kV and evaporation rate 0.1 nm / s, and then the film is cured for 30 minutes under a curing environment of 150° C. to enhance the stability of the film;

[0156] The remaining steps and parameters are the same as those in Example 1 to obtain a polarizing plate 3.

[0157] Comparative Example 4

[0158] In this comparative example 4, step S4.4 uses a diamond grinding wheel to trim the edge to ensure that the finished product size specification is 1.115 mm;

[0159] Step S5.5: Use a vernier caliper to measure the size of the finished product to ensure that the specification is 1.115 mm;

[0160] The remaining steps and parameters are the same as those in Example 1 to obtain a polarizing plate 4.

[0161] 3. Performance test:

[0162] The polarizers, polarizer 1, polarizer 2, polarizer 3 and polarizer 4 in Example 1 and Comparative Examples 1 to 4 were selected to perform performance tests on polarization degree, transmittance, optical compensation value, peel strength and thermal expansion coefficient;

[0163] It should be noted that:

[0164] (1) Polarization degree is tested using the method of GB / T 33048-2016 "Determination of optical compensation value of polarizer";

[0165] (2) The transmittance is tested using the method of GB / T 25275-2010 "Test methods for optical properties and weather resistance of polarizers for liquid crystal displays (LCDs)";

[0166] (3) The optical compensation value is tested using the method of HG / T 4183-2011 "Polarizers for Liquid Crystal Displays (LCD)";

[0167] (4) The peel strength is tested using the method of HG / T 4183-2011 "Polarizer for Liquid Crystal Display (LCD)";

[0168] (5) The thermal expansion coefficient is tested using the method of GB / T 33048-2016 "Determination of optical compensation value of polarizer";

[0169] The results are shown in Table 1:

[0170] Table 1 Performance test data of polarizer, polarizer 1, polarizer 2, polarizer 3 and polarizer 4 in Example 1, Comparative Examples 1 to Comparative Examples 4

[0171]

[0172]

[0173] According to the above data, the polarizers prepared by the processes of Example 1 of the present application and Comparative Examples 1 to 4 are all within the standard range;

[0174] At the same time, by analyzing the effects of changes in white glass thickness, polishing time, coating time, and finished polarizer size in the polarizers in Example 1, Comparative Examples 1 to 4, polarizer 1, polarizer 2, polarizer 3, and polarizer 4 on the performance by the controlled variable method, it can be seen that in the process flow of the present invention, Example 1 is better than Comparative Examples 1 to 5.

[0175] The polarizer prepared in Example 1 was then subjected to reliability test, and the data are shown in Table 2:

[0176] Table 2 Reliability test data of polarizer obtained in Example 1

[0177]

[0178]

[0179]

[0180] In summary, under the premise that the performance parameters of the polarizer in Example 1 are better, reliability experiments were conducted on it and all four tests passed. Therefore, the polarizer prepared by the process of Example 1 of the present invention is the best embodiment.

[0181] Therefore, through the above steps, the process of the present invention realizes precise control of the size, surface roughness and coating thickness of the polarizer through diamond wheel cutting, double-sided polishing machine polishing and vacuum coating machine high-precision equipment, thereby improving the performance stability of the product;

[0182] The process of the present invention improves process efficiency and product quality by using an ultrasonic cleaner to remove polishing residues and using a plasma processor to enhance surface energy;

[0183] Each step in the process of the present invention is precisely controlled, thereby improving the yield rate and reducing the production cost.

[0184] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A polarizing plate processing process, characterized in that: The following steps are involved: S1. Prepare white glass raw materials and prepare polished sheets; S2. Perform appearance and thickness inspection on the polishing sheet, and enhance the surface energy of the polishing sheet after cleaning and dust removal; S3. Performing a coating operation on the white glass 1 and the white glass 2 after the surface energy enhancement in step S2 and further performing an appearance inspection; S4. Prefabricating a polarizing film and configuring a specific ratio of adhesive, bonding and curing the polarizing film after cleaning and coating the white glass 1 and the white glass 2 by preparing a specific ratio of adhesive; S5. Cover the white glass 1 and the white glass 2 with the polarizing film in step S4 with a UV film and perform a knife wheel cutting; S6. Pre-treating the polarizer coated with UV film and cut in step S5; S7. Laminating and curing the polarizer pretreated in step S6 with Mylar sheets, and packaging and storing; S8. Select 1-2 batches from every 100 batches of polarizer products entering the warehouse for performance testing and reliability testing.

2. A polarizing plate processing process according to claim 1, characterized in that: The implementation steps of step S1 are: S1.

1. Use high-purity silicate glass original sheets, the thickness of white glass 1 is 0.30±0.015mm, the thickness of white glass 2 is 0.55±0.015mm, ensure there are no bubbles or scratches, use an optical detector to detect the glass surface quality, and ensure that the transmittance is ≥92%; S1.

2. Use a precision diamond wheel to cut the glass sheet into 100mm×100mm to 200mm×200mm with a cutting accuracy of 0.05mm, and then perform edge chamfering with a chamfer angle of 45° and a chamfer width of 0.1mm to reduce the risk of breakage in subsequent processing; S1.

3. Prepare a polishing solution containing SiO2 particles with a particle size of 0.5 μm and a surfactant, the ratio of the polishing solution to the surfactant is 50 grams per liter of solution, and the pH value is controlled at 7.0 ± 0.5 to ensure the polishing effect; S1.

4. Use a double-sided polishing machine and set the speed to 1500rpm, polishing time to 30min, and pressure to 20kPa to polish white glass 1 and white glass 2, ensuring that the glass surface roughness Ra≤0.01μm and the light transmittance is greater than 94%; S1.

5. Use an ultrasonic cleaner to clean the polished white glass 1 and white glass 2 three times with deionized water and anhydrous ethanol alternately for 5 minutes each time to remove polishing residues. After cleaning, dry them in an oven at 60°C for 1 hour.

3. A polarizing plate processing process according to claim 1, characterized in that: The implementation steps of step S2 are: S2.

1. Use a 10x magnifying glass to check the surface of the polished sheet to ensure there are no cracks or scratches; S2.

2. Use a micrometer to measure the thickness of each piece of glass, ensuring that the thickness of white glass 1 is 0.30±0.015mm and that of white glass 2 is 0.55±0.015mm; S2.

3. Immerse the polishing sheet in a dilute hydrochloric acid solution with a pH of 2.5 for 5 minutes to remove metal ion contamination, and then neutralize it with a dilute sodium hydroxide solution with a pH of 10.5 for 3 minutes; S2.

4. Rinse with deionized water three times, 2 minutes each time, to ensure that there is no residual acid or alkali, then air dry naturally in a dust-free environment or blow dry with nitrogen, and wipe the surface with a dust-free cloth; S2.

5. Treat the surface with a plasma processor at 100W for 10 seconds to enhance the adhesion of subsequent coatings.

4. A polarizing plate processing process according to claim 1, characterized in that: The implementation steps of step S3 are: S3.

1. Place the polished sheets of white glass 1 and white glass 2 on the stage of the vacuum coating machine and evacuate to 10-4Pa; S3.

2. MgF2 with high light transmittance and low refractive index and a thickness of 50 nm was selected as the coating material. The coating time was 5 min under the coating process parameters of electron beam energy of 20 kV and evaporation rate of 0.1 nm / s. The film was then cured at 150°C for 30 min to enhance the stability of the film. S3.

3. Use a 50x optical microscope to check the uniformity of the coating, including peeling and cracking; S3.

4. Use a transmittance tester to ensure that the transmittance after coating is greater than 93%, and measure the surface roughness again to ensure that Ra ≤ 0.02μm.

5. A polarizing plate processing process according to claim 1, characterized in that: The implementation steps of step S4 are: S4.

1. Select a 0.215 mm thick polyvinyl alcohol polarizing film and cut it to a size that matches the coated white glass 1 and white glass 2; S4.

2. Soak the polarizing film in anhydrous ethanol for 5 min, and then rinse it with deionized water twice, 1 min each time; S4.

3. Place the polarizing film between the white glass 1 and the white glass 2 and perform a composite operation by using an adhesive. The specific bonding structure is as follows: Clear glass 1+polarizing film+clear glass 2; Apply the adhesive, use a vacuum press, set the pressure to 0.5MPa, and the time to 15min, and initially cure in a 60℃ oven for 2 hours. After the time is up, raise the temperature to 80℃ and cure for another 4 hours to ensure that the adhesive is completely cured; S4.

4. Use a diamond grinding wheel to trim the edges and ensure that the finished product size specification is 1.10±0.015mm.

6. A polarizing plate processing process according to claim 5, characterized in that: The adhesive in step S4 is specifically obtained by mixing T-31 phenolic amine (PAA) and epoxy curing agent in a ratio of epoxy resin: curing agent of 100:

5.

7. A polarizing plate processing process according to claim 1, characterized in that: The implementation steps of step S5 are: S5.

1. Select a 0.05 mm thick UV curing film and cut it to a size that matches the polarizer, and ensure that it is consistent with the finished product size in step S4; S5.

2. Apply a layer of UV glue evenly on the surface of the polarizer and compact it with a roller. The coating ratio of UV glue is 50 grams per square meter. S5.

3. Use a UV curing machine, set the wavelength to 365nm, the energy density to 1000mJ / cm², and perform a curing operation for 10 seconds; S5.

4. Use a precision diamond wheel with a cutting accuracy of 0.02 mm to cut the polarizer to the finished size, grind the cut edge with a fine grinding wheel to ensure smoothness and no burrs, and wipe the surface with a dust-free cloth moistened with 1 / 3 of anhydrous ethanol to remove debris generated by cutting; S5.

5. Use a vernier caliper to measure the finished product size and ensure that the specification is 1.10±0.015mm.

8. The process for processing a polarizing plate according to claim 1, characterized in that: The implementation steps of step S6 are: S6.

1. Use a plasma processor with a power of 80W to perform surface activation treatment for 5 seconds to increase surface energy for subsequent bonding; S6.

2. Spray antistatic agent and let it stand for 5 minutes to ensure that the surface resistivity is less than 10^9Ω; S6.

3. Use a magnifying glass to check the surface to ensure that there are no foreign objects or scratches. Then prepare the Mylar sheet and cut it to a size that matches the polarizer with an error range of ±0.05mm. Align the Mylar sheet with the polarizer and fit them together at a pressure of 0.1±0.05MPa to ensure that there are no bubbles. Use epoxy resin glue to seal the edges to prevent water vapor intrusion.

9. The process for processing a polarizing plate according to claim 1, characterized in that: The implementation steps of step S7 are: S7.

1. Attach the Mylar sheet to the surface of the polarizer and use a vacuum press to press for 10 minutes at a pressure parameter of 0.3 MPa; S7.

2. Curing in a 60°C oven for 1 hour to ensure a firm fit; S7.

3. Use an anti-static packaging bag that is slightly larger than the polarizer. Make sure the bag can completely wrap the polarizer and have enough space for sealing. Put the polarizer into the bag and seal it with a heat sealer. S7.

4. Use a transmittance tester to test the transmittance. The qualified standard is whether it is greater than 90%. Put the packaged and qualified polarizers in a dry and ventilated warehouse with an ambient temperature of 20~25℃ and a humidity of 40~60%.

10. The process for processing a polarizing plate according to claim 1, characterized in that: The performance tests in step S8 include polarization, transmittance, optical compensation value, peel strength and thermal expansion coefficient tests, and the reliability tests in step S8 include water boiling film drawing, high temperature storage, low temperature storage, high and low temperature storage and hot and cold shock tests.